Under pressure of two dictatorships: Mensheviks of Urals and TransUrals in first months of A. V. Kolchak’s dictatorship - V. V. Moskovkin; I. V. Skipina (Омский научный вестник: Серия "Общество. История. Современность")
The experience of political parties gained in the years of the Civil War in a multiparty environment is instructive. The purpose of this article is to show that the dual position taken by the Menshevik organizations in the first months of Kolchak’s dictatorship exacerbated the already tense struggle in the regions and did not contribute to the popularity of the party. An analysis of the political line of the Mensheviks testifies to the inconsistency of their ideological position, which in conditions of tough confrontation could not become the key to the success of the party claiming a leading position in governing the country. In the fall of 1918, the Mensheviks demonstrated opposition to any dictatorship, expressed disagreement with the Bolshevik policies, they did not support Kolchak, continuing to defend the «third way» in the revolution, believing he would ensure the victory of democracy and socialism and allow to form republican rule. As a result, the Mensheviks were under the pressure of two dictatorships: proletarian and military. Persecuted by both the Bolshevik and Kolchak authorities, they were swept from the arena of political struggle